Effect of Immersion Eggs using Viamin C on Hatching Rate, Growth, and Survival Rate of Asian Redtail Catfish Larvals (Hemibagrus nemurus) - Nur Rohman Shafudin; Nuraini Nuraini; Netti Aryani (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2023)
This research was carried out for 40 days from December 2021 to January 2022 at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine, Riau University, Pekanbaru. This study aimed to find out the effect of immersion eggs with different doses of vitamin C on egg hatchability, growth, and survival of Asian redtail catfish larvae and to find out the best dose of vitamin C for immersion Asian redtail catfish eggs. This study used a one-factor completely randomized design with four treatments with three replications. The treatments used were P0 (control), P1 using vitamin C 50 mg/L, P2 using vitamin C 100 mg/L and P3 using vitamin C 150 mg/L. Immersion Asian redtail catfish eggs using different doses of vitamin C had a significantly different effect (P<0.05) on the degree of fertilization, hatching rate, weight growth, length growth, specific growth rate, and survival rate of Asian redtail catfish larvae. The best dose of vitamin C for immersion Asian redtail catfish eggs is a dose of 150 mg/L with of 93.18% degree of fertilization, hatching rate of 86.24% absolute weight growth of 2.25 g, absolute length growth of 6.32 cm, the specific growth rate is 10.08% and the survival rate is 91.11%. The range of water quality obtained during the research supports hatching and rearing of Asian redtail catfish larvae, the temperature range is between 26.5 C to 27 C, water pH is 5.9 to 7 and dissolved oxygen is 4.9 to 6.